Pengaruh Environmental, Social, Governance (ESG) dan Financial Distress terhadap Firm Value Sektor Energi yang Terdaftar di BEI Tahun 2020-2024 - Lediana Sufina; Pratiwi, Tariza Andini; Maharani, Sabiikha Putri; Putri, Amelia Reza (STIE Indonesia Banking School, 2024)
In the face of accelerating global warming, Indonesia’s mining industry continues to exploit natural resources on a large scale. While some companies have begun to adopt sustainability practices, many are still lagging behind. At the same time, several mining firms are experiencing declining financial conditions. This study examines whether ESG performance and financial distress influence firm value. Using a sample of mining companies listed on the Indonesia Stock Exchange from 2020 to 2024, firm value is measured using Tobin’s Q, ESG performance by ESG index scores based on Global Initiative Reporting (GRI), and financial distress by the Altman Z-Score. Panel data regression is employed to analyze relationships. The findings are expected to provide insights into whether sustainability efforts and financial health contribute to higher firm value, and to support stakeholders in promoting responsible and resilient growth in Indonesia’s mining sector. The results show that ESG performance has a positive but not significant effect on firm value, while financial distress has a positive and significant effect. These findings provide insights into whether sustainability efforts and financial health contribute to higher firm value, and support stakeholders in promoting responsible and resilient growth in Indonesia’s mining sector.